Identification of epidemiological risk factors associated with missed abortion in polycystic ovary syndrome: a retrospective analysis - Shuting Yu; Yuan Yuan (BMC Pregnancy and Childbirth)
Abstract Background Patients with polycystic ovary syndrome (PCOS) face a greater risk of miscarriage during pregnancy. However, the relationship between PCOS and missed abortion (MA) has not been comprehensively studied. Method This retrospective study included 194 pregnant women with PCOS, diagnosed using the 2004 Rotterdam criteria. Participants were categorized into the MA group (n = 100) or the control group (term live births, n = 94) based on pregnancy outcomes. Baseline characteristics and clinical features were collected, and statistical analyses were performed to identify MA risk factors. Results At baseline, the MA group had a lower BMI (p = 0.000) and higher educational level (p = 0.026) compared to the control group, with no significant differences in other baseline characteristics. Regarding clinical features, significant differences were observed in conception method, menstrual period duration, menstrual patterns, total testosterone, fasting insulin, and anti-Müllerian hormone (AMH) levels. After adjusting for BMI and educational level, univariate analysis identified oligomenorrhea (OR = 10.502, p = 0.000), menstrual period duration (OR = 1.888, p = 0.002), total testosterone (OR = 1.047, p = 0.009), and AMH (OR = 1.286, p = 0.044) as significant risk factors. Multivariate logistic regression confirmed that menstrual period duration (OR = 2.074, p = 0.003), oligomenorrhea (OR = 12.487, p < 0.001), and total testosterone (OR = 1.067, p = 0.003) were independently associated with MA risk in PCOS patients. Conclusion This study identifies menstrual period duration, oligomenorrhea, and total testosterone as independent risk factors for MA in women with PCOS. These findings highlight the importance of monitoring menstrual irregularities and hormonal profiles to optimize pregnancy outcomes in PCOS patients.